2008
DOI: 10.1152/ajpgi.00173.2007
|View full text |Cite
|
Sign up to set email alerts
|

Saccharomyces boulardiiamelioratesCitrobacter rodentium-induced colitis through actions on bacterial virulence factors

Abstract: Saccharomyces boulardii has received increasing attention as a probiotic effective in the prevention and treatment of infectious and inflammatory bowel diseases. The aim of this study was to examine the ameliorating effects of S. boulardii on Citrobacter rodentium colitis in vivo and identify potential mechanisms of action. C57BL/6 mice received 2.5 x 10(8) C. rodentium by gavage on day 0, followed by S. boulardii (25 mg; 5 x 10(8) live cells) gavaged twice daily from day 2 to day 9. Animal weights were monito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
99
0
3

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(103 citation statements)
references
References 62 publications
1
99
0
3
Order By: Relevance
“…Z kolei Bifidobacterium longum wytwarza substancję wiążącą toksynę Vero produkowaną przez EHEC, zapobiegając w ten sposób jej wiązaniu się z komórkami nabłonka jelitowego (26). Saccharomyces boulardii hamuje zaś wytwarzanie przez Citrobacter rodentium czynników zjadliwości EspB i Tir uczestniczących w adherencji tych bakterii do komórek nabłonka (55).…”
Section: Kompetycyjne Wykluczanieunclassified
“…Z kolei Bifidobacterium longum wytwarza substancję wiążącą toksynę Vero produkowaną przez EHEC, zapobiegając w ten sposób jej wiązaniu się z komórkami nabłonka jelitowego (26). Saccharomyces boulardii hamuje zaś wytwarzanie przez Citrobacter rodentium czynników zjadliwości EspB i Tir uczestniczących w adherencji tych bakterii do komórek nabłonka (55).…”
Section: Kompetycyjne Wykluczanieunclassified
“…These effects have been assessed in several studies and showed that S. boulardii exerts beneficial mechanisms in animal models displaying IBD as well as in pathogenic or opportunistic micro-organism infection models such as Clostridium difficile, Vibrio cholerae, Escherichia coli, Salmonella enterica subspecies enterica serovar Typhimurium, Shigella flexneri, Citrobacter rodentium and Candida albicans Czerucka et al, 1994;Dahan et al, 2003;Dalmasso et al, 2006b;Jawhara and Poulain, 2007;Mumy et al, 2007;Wu et al, 2008). These mechanisms include the modification of host cell signalling pathways implicated in proinflammatory response and in hydroelectrolytic secretion, the stimulation of host immune defences, the neutralization of bacterial toxins and the decrease of bacterial adherence to intestinal epithelial cells, the maintenance of membrane permeability and the inhibition of pathogen translocation.…”
Section: Experimental Effects Of Saccharomyces Boulardiimentioning
confidence: 99%
“…In addition to serving as model for EPEC and EHEC infection in small-animal, C. rodentium can also serve as model for inflammatory bowel disease in mouse (Higgins et al, 1999). Recently, the beneficial effect of S. boulardii on C. rodentium-induced colitis was assessed in mice (Wu et al, 2008). The improvement effect of S. boulardii was associated with significantly reduced numbers of mucosal adherent bacteria compared with infected untreated animals (P < 0.05).…”
Section: Decrease Of Bacterial Adhesion To Intestinal Epithelial Cellsmentioning
confidence: 99%
“…Some of the basic mechanisms by which the probiotics confer health benefits to the host include modulating the mucosal barrier function, decreasing the apoptosis of epithelial cells and by increasing mucin production (Mattar et al 2002;Gaudier et al 2005;Yan and Polk 2006;Caballero-Franco et al 2007;Gogineni et al 2013;Saad et al 2013), aiding the increased production of antimicrobial peptides like defensins and cathelcidins by host cells (Schlee et al 2008;Kelsall 2008;Mondel et al 2009), production of bacteriocins, microcins and other antimicrobial substances that make the intestinal environment less comfortable for other pathogenic microbes (especially by lowering pH) (Alakomi et al 2000;Penner et al 2005;Liévin-Le et al 2006;Duquesne et al 2007;Venkateshwari et al 2010;Vijayendra et al 2010;Halami et al 2011;Sharma and Devi 2014), adhering to the epithelial cells in a competitive fashion and by blocking the adherence of pathogens on the epithelial cells either directly or indirectly (Johnson-Henry et al 2007;Wu et al 2008), modulating the immune system, by blocking pro-inflammatory molecules and by increasing mucin production (Ogawa et al 2001;Tien et al 2006) and interfering with the quorum sensing signaling, process through which the pathogenic microbes communicate with one another (Miller and Bassler 2001;Medellin-Peña et al 2007). …”
Section: Introductionmentioning
confidence: 99%